Hybridization of Neural Nets and Genetic Algorithms to Compute the Boundary Control for Controlled Heat Equation (European Journal of Pure and Applied Mathematics, 2011)
This paper presents a computational method for boundary control of controlled heat equation. The proposed method relies upon the function approximationcapability of feedforward neural network and global optimizationpower of genetic algorithm.